기립상태에서 비정상적 무릎관절 굴곡에 대한 보존적 치료 임상사례연구 - 조일영(Il-Young Cho) (한국콘텐츠학회 논문지, 9(1), 2009)
Objectives: There are many reasons to restrict extension of knee. Unless we can find any structural deformities from patients, we don't have any clue of helping this condition except give them some instruction of exercise of strengthening anterior thigh muscles and releasing extensor muscle group of lower extremities. In this study, the author reports new case, using technique of releasing restriction of knee movement based on Sacro Occipital Technique. Method: From the day of notifying 14yrs. old patient's extension restriction of knee, it had have 7 trials of having S.O.T category Ⅰ. technique procedure. Result: The patient can stand without extension restriction of knee. Conclusion: In many case, muscle soft tissue work helps releasing hamstring tension so that we can make patient stand with straightly extended knee position but if this method is not working then S.O.T category Ⅰ. technique procedure may be considerable to improve this condition. 무릎의 신전이 방해되는 이유는 여러 가지가 있다. 하지만 우리가 특별히 구조적인 기형을 환자에게서 찾아내지 못하는 한 넙다리근육 강화나 신전을 위한 하지 폄근육군 완화운동 방법을 알려주는 것 이외에 별달리 해줄 수 있는 것이 없다. 이 연구에서 저자는 Sacro-Occipital Technique을 활용한 무릎 움직임 방해 완화에 대하여 새로운 사례연구를 하였다. 이 연구에서는 무릎을 완전히 펴고 서지 못하는 14세의 여학생에게 7회의 S.O.T categoryⅠ. 방법이 적용되었으며 이로서 별다른 방해 없이 무릎을 펴고 설수 있게 되었다. 대체적으로 무릎을 곧바로 펴지 못하는 많은 경우 근육 연조직 마사지 등을 뒤넙다리근에 적용하여 완화 시켜 보기도 한다. 그러나 만약 이러한 방법들이 잘 듣지 않는다면 S.O.T categoryⅠ. 방법을 고려하여 보는 것도 도움이 될 수 있을 것으로 사료된다.